COVID‐19 convalescent plasma cohort study: Evaluation of the association between both donor and recipient neutralizing antibody titers and patient outcomes. Issue 8 (8th July 2021) - Yokoyama, Ana Paula H.; Wendel, Silvano; Bonet‐Bub, Carolina; Fachini, Roberta M.; Dametto, Ana Paula F.; Blumm, Fernando; Dutra, Valeria F.; Candelaria, Gabriela T. P.; Sakashita, Araci M.; Machado, Rafael Rahal Guaragna; Fontão‐Wendel, Rita; Hamerschlak, Nelson; et al.
Abstract: Background: Current evidence regarding COVID‐19 convalescent plasma (CCP) transfusion practices is limited and heterogeneous. We aimed to determine the impact of the use of CCP transfusion in patients with previous circulating neutralizing antibodies (nAbs) in COVID‐19. Methods: Prospective cohort including 102 patients with COVID‐19 transfused with ABO compatible CCP on days 0–2 after enrollment. Clinical status of patients was assessed using the adapted World Health Organization (WHO) ordinal scale on days 0, 5, and 14. The nAbs titration was performed using the cytopathic effect‐based virus neutralization test with SARS‐CoV‐2 (GenBank MT126808.1). The primary outcome was clinical improvement on day 14, defined as a reduction of at least two points on the adapted WHO ordinal scale. Secondary outcomes were the number of intensive care unit (ICU)‐free days and the number of invasive mechanical ventilation‐free days. Results: Both nAbs of CCP units transfused ( p < 0.001) and nAbs of patients before CCP transfusions ( p = 0.028) were associated with clinical improvements by day 14. No significant associations between nAbs of patients or CCP units transfused were observed in the number of ICU or mechanical ventilation‐free days. Administration of CCP units after 10 days of symptom onset resulted in a decrease in ICU‐free days ( p < 0.001) and mechanical ventilation‐free days ( p < 0.001). Conclusion: Transfusion of high titer nAbs CCP units may be a determinant in clinical strategies against COVID‐19. We consider these data as useful parameters to guide future CCP transfusion practices.